2016
DOI: 10.3390/ijms17111800
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Angiotensinogen Could Be a Prognostic Marker of the Renoprotection of Olmesartan in Metabolic Syndrome Patients

Abstract: This study was performed to demonstrate urinary angiotensinogen as a potential prognostic marker of the albuminuria reduction effects of olmesartan in patients with metabolic syndrome. In 24 patients (eight women, 57.88 ± 2.00 years), 5–40 mg/day of olmesartan were given. Urinary concentrations of albumin and angiotensinogen (normalized by urinary concentrations of creatinine) and plasma renin activity were measured before and after the 12- and 24-week marks of olmesartan treatment. Olmesartan treatment increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…Regarding the renal protective effects, urinary albumin and u-AGT both tended to decrease in the olmesartan group, as observed in the study by Mizushige et al [17]. These authors reported that urinary albumin and u-AGT simultaneously decreased after olmesartan was administered to patients with metabolic syndrome [17]. The present study, which included few hypertensive patients with metabolic syndrome (olmesartan group: body mass index, 24), showed a similar tendency.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Regarding the renal protective effects, urinary albumin and u-AGT both tended to decrease in the olmesartan group, as observed in the study by Mizushige et al [17]. These authors reported that urinary albumin and u-AGT simultaneously decreased after olmesartan was administered to patients with metabolic syndrome [17]. The present study, which included few hypertensive patients with metabolic syndrome (olmesartan group: body mass index, 24), showed a similar tendency.…”
Section: Discussionsupporting
confidence: 86%
“…The antihypertensive effect observed in this subanalysis was comparable to that observed in the CANZONE study [1] and the MUSCAT-4 study [2]. Regarding the renal protective effects, urinary albumin and u-AGT both tended to decrease in the olmesartan group, as observed in the study by Mizushige et al [17]. These authors reported that urinary albumin and u-AGT simultaneously decreased after olmesartan was administered to patients with metabolic syndrome [17].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 7 These data indicate that the diuretic effect of a SGLT2 inhibitor is soon compensated for, possibly by an adaptive physiological mechanism. In this regard, Cherny et al 8 reported that urinary angiotensinogen (AGT) excretion, which reflects intrarenal renin–angiotensin system (RAS) activity, 9 , 10 was significantly increased by treatment with a SGLT2 inhibitor in patients with type 1 diabetes mellitus. These data suggest that intrarenal RAS is activated to compensate for acute loss of sodium and body fluid.…”
mentioning
confidence: 99%